Tragedi dalam Relasi Ayah dan Anak dalam Film Farha (2021): Kajian Psikoanalisis Jacques Lacan - Ishlah Rodiyah Assufi; Misbahus Surur (RETORIKA: Jurnal Ilmu Bahasa, 2025)
The film Farha (2021) tells the story of a deep emotional relationship between a father and his daughter against the background of the Israeli occupation of Palestinian settlements, in a major event that gripped and became a dark memory of the Palestinian people known as the Nakba. Farha's movie provides rich interpretative potential related to identity formation in the psychoanalytic realm. This research aims to reveal the emotional relationship between Farha and her father, in forming the objectivity structure of the main character through Lacan's miror stage concept. The research method was descriptive qualitative, employing Jacques Lacan's psychoanalytic approach. Data were collected through repeated viewings of the film, noting key scenes, dialogue, gestures, and symbols. Data were then analyzed by grouping the scenes into the Imaginary, Symbolic, and Real domains, in accordance with Lacan's theory. The results of this study show that the father figure in the film functions double: as a mirror of ideal identity and ego (the realm of the imaginary), as a representative of symbolic norms and laws (the realm of the symbolic), and as a source of existential wounds in traumatic experiences (the realm of the Real). This finding implies that cinematic works such as Farha's film are effective as a reflective field to understand individual psychological dynamics shaped by family, symbolic and trauma forces, and supports the development of interdisciplinary studies based on humanities and psychoanalysis.